Rapid degradation of anionic azo dye from water using visible light-enabled binary metal-organic framework - Mustafa, Faisal Suleiman; Oladipo, Akeem Adeyemi (Elsevier, 2024)
Bimetallic organic frameworks (Mn-Al-MOF) were synthesized using a hydrothermal technique and used as a photocatalyst to degrade EBT dye. The physicochemical features of Mn-Al-MOF were analyzed using various advanced techniques. SEM micrographs showed that Mn-Al-MOF has uneven faceted networks that are not perfect spheres or cubes. The average particle size is 36.9 nm. Furthermore, Mn-Al-MOF has a bandgap energy of 2.95 eV, an average pore diameter of 4.82 nm, and a total pore volume of 0.195 cm(3)/g. When 10.0 mg of Mn-AlMOF was used, 87.2 % of 10.0 ppm EBT was removed in the dark within 60 min. However, under visible light irradiation and with 1.0 mM K2S2O8, 5.0 mg of Mn-Al-MOF showed enhanced and rapid photocatalytic properties, resulting in 100 % degradation of EBT. The degradation rate constant of 0.0169 s(-1) under optimized conditions in the presence of visible light irradiation was 24.8 times higher than using 5.0 mg Mn-Al-MOF in the dark. Mn-Al-MOF exhibited 84.9-100 % degradation efficiency in a binary mixture of dyes and can be effectively reused over multiple recycling stages. The photodegradation activity was dominated by O-2(center dot-), (OH)-O-center dot, and SO4 center dot-, with sulfate radicals playing a dominant role. The mechanisms involved in the adsorption and photocatalysis stages were also discussed. According to the cost analysis results, it will cost 0.49 US $ to treat 1.0 L of 10.0 ppm EBT dye solution containing interference using 0.20 g/L. Mn-Al-MOF is a potentially effective catalytic material with rapid degradation efficiency and high stability.
Keywords: Textile dye effluent; Visible light-activated; MOF; Degradation mechanism; Photocatalyst